(untitled) (Third Sector Social Economic Review, 2025)
The purpose of this study is to examine how students and teachers perceive ""school"" and ""school during the pandemic"" through metaphorical images. Conducted as a qualitative, hermeneutic phenomenological study, it involves 202 teachers and 244 students from public middle schools during the 2022-2023 academic year. Data were collected using semi-structured, open-ended online questionnaires and analyzed through content analysis, resulting in codes, categories, and themes derived from participant metaphors.Findings reveal that teachers perceive school as a nurturing, safe environment akin to family, a process requiring effort, and a space for preparing individuals for life through knowledge. Students similarly describe school as a source of wisdom, a reflection of life filled with joy, sadness, and friendships, and a protective home. However, during the pandemic, teachers viewed school as an empty, aimless structure detached from life, while students perceived it as an intangible, ambiguous place experienced only through technology. The study highlights the pandemic’s significant influence on school perceptions, reinforcing the view of schools as essential social environments beyond academics. It underscores the importance of face-to-face education and social interaction in promoting resilience and managing stress during crises.